Ce Cation Migration and Diffusivity in Perfluorosulfonic Acid Fuel Cell Membranes. (3rd July 2019) - Baker, Andrew M.; Komini Babu, Siddharth; Chintam, Kavitha; Kusoglu, Ahmet; Mukundan, Rangachary; Borup, Rod L.
Abstract : A hydrogen pump experiment was utilized to simultaneously determine the migration and diffusivity of Ce ions in perfluorosulfonic acid (PFSA) ionomer membranes over a range of temperatures and relative humidities. Ce ion migration profiles were quantified as a function of charge transfer through the cell using X-ray fluorescence (XRF). Competing transport phenomena were decoupled by fitting XRF profile data with our previously-developed one-dimensional model, which was updated with improved conductivity and water uptake relations. Measured transport values showed good agreement with the Einstein relation and Okada transport theory, implying that conductivity can be used to estimate migration and diffusivity of cations in other cation/PFSA systems. Results presented here may be used to populate device-level models in order to further understand the effects of cation transport on fuel cell performance and durability to determine the mitigation controls for cation stabilization.